PEMBENTUKAN KELOMPOK KADER DAN IBU “SAGITA” (Sayang Ibu dan Balita) SEBAGAI UPAYA PENCEGAHAN STUNTING - Kurnia kurnia; Retno Issroviatiningrum (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2023)
toddlers. Indonesia, which is a developing country, contributes to the growth in the stunting rate in toddlers in the world where currently Indonesia is ranked fifth in the world's incidence of stunting in toddlers. Stunting can be prevented by community empowerment activities, namely village involvement in detecting and preventing stunting. The purpose of this community service activity is to improve health status by forming a community, especially cadres and mothers who are aware of stunting "SAGITA" (Sweet Mothers and Toddlers) in Bandarharjo Village. Bandarharjo Village was chosen because it is part of the working area of ​​the Bandarharjo Health Center, North Semarang. With data on stunted children in June 2021, there were 86 stunted children aged 0-60 months, of which 60 (70%) were short children and 26 (30%) were very short children. 738 souls the number of normal toddlers. Meanwhile, data on stunted children in the Bandarharjo sub-district, North Semarang in June 2021, with data on toddlers aged 24-59 months, 26 people were very short, 60 people were short, and there were 60 toddlers who contributed to stunting at ages 48-60 months, male and female. The World Health Organization (WHO) since 2007 has socialized the Community-Based Management of Severe Acute Malnutrition program. One approach that can be taken is community empowerment. The "SAGITA" community service activity in Bandarharjo Village is preparing tools, health promotion media, and places used for program implementation. Activities in this community service consist of forming a group of mothers who are aware of nutrition, training on toddler development screening for cadres, counseling on breast milk (ASI) and complementary foods for breast milk (MPASI), counseling on balanced nutrition, hand washing training for pre-school children, and stimulate toddler development. Evaluation of this activity is carried out by measuring mother's knowledge related to nutrition and measuring the nutritional status of toddlers.